Medea in the courtroom and on the stage in nineteenth century London - Goc, Nicola Elizabeth (Australasian Journal of Victorian Studies, 2009)
In 430 BC Greek playwright Euripides transformed the mythological figure of Medea into the proto-typical murdering mother when he put a dagger in her hand and had her slaughter her two young sons. Euripides, at the same time, created the only known ancient version of the classic legend to portray Medea sympathetically. It is this combination of sympathy power and repulsion that has seen Euripides’ Medea endure down through the ages. In nineteenth-century London adaptations of Euripides’ play struck a chord with audiences at a time when unprecedented numbers of English mothers were killing their babies. At a time when it was claimed that London harboured 16,000 women who had destroyed their children (Behlmer, Child Abuse 23) Medea was the most ubiquitous heroine of the London stage. While Medea on the London stage was the object of public gaze, so too were the real-life Medeas of London, who were charged with infanticide and stood in the dock of the Old Bailey, or in a room set aside for inquests at a public inn. This paper examines the intersections between the imagined Medea of the nineteenth-century London stage and real-life Medeas of the London streets by analysing editorial texts in London’s most influential nineteenth-century newspaper, the London Times. I will draw upon news reports of infanticide trials and inquests, editorials and letters to the editor, and on theatre reviews and news stories about theatre performances and performers, to map both the 19th century stage persona of Medea and the experience of young abandoned mothers driven to murder their children.